Abnormal expression of the genes involved in cytokine networks and mitochondrial function in systemic juvenile idiopathic arthritis identified by DNA microarray analysis. Issue 2 (3rd April 2008) - Ishikawa, S; Mima, T; Aoki, C; Yoshio-Hoshino, N; Adachi, Y; Imagawa, T; Mori, M; Tomiita, M; Iwata, N; Murata, T; Miyoshi, M; Takei, S; et al.
Abstract : Objectives: Systemic juvenile idiopathic arthritis (sJIA) is a rheumatic disease in childhood characterised by systemic symptoms and a relatively poor prognosis. Peripheral leukocytes are thought to play a pathological role in sJIA although the exact cause of the disease is still obscure. In this study, we aimed to clarify cellular functional abnormalities in sJIA. Methods: We analysed the gene expression profile in peripheral leukocytes from 51 patients with sJIA, 6 patients with polyarticular type JIA (polyJIA) and 8 healthy children utilising DNA microarrays. Gene ontology analysis and network analysis were performed on the genes differentially expressed in sJIA to clarify the cellular functional abnormalities. Result: A total of 3491 genes were differentially expressed in patients with sJIA compared to healthy individuals. They were functionally categorised mainly into a defence response group and a metabolism group according to gene ontology, suggesting the possible abnormalities in these functions. In the defence response group, molecules predominantly constituting interferon (IFN)γ and tumour necrosis factor (TNF) network cascades were upregulated. In the metabolism group, oxidative phosphorylation-related genes were downregulated, suggesting a mitochondrial disorder. Expression of mitochondrial DNA-encoded genes including cytochrome c oxidase subunit 1(MT-CO1) and MT-CO2 were suppressed in patients with sJIA but not in patients with polyJIA or healthy children. However, nuclear DNA-encoded cytochrome c oxidases were intact. Conclusion: Our findings suggest that sJIA is not only an immunological disease but also a metabolic disease involving mitochondria disorder.